Rusip with Alginate Addition as Seasoning - Dyah Koesoemawardani; Mahrus Ali (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractRusip was a fermented food of fish that have a distinctive aroma so that potential to be developed into instant seasoning. This research was aimed to optimize powder processing of rusip with the addition of alginate. The treatments were concentration of alginate (5% , 10% , 15% and 20% w/w) and the heating temperature (50oC, 60oC , 70oC and 80oC). Data was analyzed using advanced test Honestly Significant Difference (HSD) at 5% level. The results showed that the best rusip powder was alginate 5% with heating at 50oC and 70°C . The character were 5.98% and 7.57% water content; pH 5.69 and 5.85; 7.77% and 8.77% salt content; 28% and 27.65% protein content, respectively. This study proves that the addition of alginate 5% (w/w), heating at a temperature of 50oC and 70°C can trap volatile compounds formed during fermentation in rusip processing into powder.